Amalan terbaik di Pusat Maklumat dan Perpustakaan (INFOLIB) Bernama - Ibrahim, Hasnita (Persatuan Pustakawan Malaysia, 2013)
InfoLib is a an information centre and library specifically for news. It has been operating since April 1968 and is a part of Bernama which is a national news agency. This article presents an overview of the best practices that are in place at InfoLib.